Socio‐economic outcomes among long‐term childhood acute lymphoblastic leukaemia survivors enrolled between 1971 and 1998 in EORTC CLG studies: Results of the 58LAE study. (25th October 2022) - Barbati, Melissa; Kicinski, Michal; Suciu, Stefan; Mazingue, Françoise; Vandecruys, Els; Plat, Geneviève; Uyttebroeck, Anne; Paillard, Catherine; Dresse, Marie‐Françoise; Simon, Pauline; Pluchart, Claire; Minckes, Odile; et al.
Abstract: Objective: The objective of this study is to evaluate the socio‐economic outcomes of survivors of childhood acute lymphoblastic leukaemia (ALL). Methods: Childhood ALL adult survivors, enrolled in EORTC trials between 1971 and 1998 in France and Belgium, were invited to fill out a questionnaire with information about their socio‐economic situation (living with a partner, having a university degree, having a job, working part time and history of having a paid job). The outcomes were compared with two matched control populations. Results: Among 1418 eligible patients, 507 (35.8%) participated, including 39 (8%) and 61 (12%) patients who received a haematopoietic stem cell transplantation (HSCT) and a cranial radiotherapy (CRT), respectively. The median time to follow‐up was 20 years, and median age was 25 years. Survivors showed a socio‐economic level at least as good as controls. HCST and CRT were associated with a higher probability of not obtaining a bachelor degree (respectively OR = 3.49, 95% CI: 1.46–8.35 and OR = 2.31, 95% CI: 1.04–5.15), HSCT was associated with unemployment (OR = 2.89, 95% CI: 1.09–7.65) and having a relapse was associated with a higher probability of not having a partner (OR = 1.88, 95% CI: 1.01–3.51) adjusting for confounders. Conclusion: Childhood ALL survivors showed a high level of socio‐economic participation. HCST and CRT were associated with poorer functioning.